Dancing through fire - Lasky, Kathryn (Portraits, 2005)
Sylvie dreams of being a prima ballerina. When the Franco-Prussian war begins in 1870, Sylvie is thrown into turmoil and tragedy. Sylvie must rely on the strength that ballet gives her in order to survive and achieve her goal.